Pendekatan Bimbingan dan Konseling Berbasis Kearifan Lokal Pesantren - Siti Fatimah Junita Sari; Iffah Nur Fidyatin (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2025)
Life in Pesantren not only develops unique cultural values of the archipelago, but also Islamic values in a culture of behavioral change by prioritizing principles such as education (ta'dib), paying attention to social situations and conditions (i'tibar ahwal an-nas), and gradual implementation (at-tadrij). In this context, it is important to consider the application of guidance and counselling pesanren theory so that the guidance and counselling process is in accordance with the context of the conditions of santri/students in Islamic boarding school-based educational institutions. This research uses library research methods and content analysis as data analysis techniques. The research results show that the role of Islamic boarding school guidance and counselling is not only in shaping behaviour, but also in developing the interests and talents of students so they can compete with advances in general science. The function of Islamic boarding school guidance and counselling is a preventive and curative function which is translated into several positive activities in the form of a study of akhlakul karimah, a student's etiquette towards his father and mother, a santri's etiquette towards his Ustadz/Ustadzah, learning etiquette, and other etiquette that will prevent him from doing bad or negative thing.